Use of a synthetic form Avrodes for transfer of leaf rust resistance from Aegilops speltoides to common wheat - R. O. Davoyan; I. V. Bebyakina; E. R. Davoyan; D. S. Mikov; E. D. Badaeva; I. G. Adonina; E. A. Salina; A. N. Zinchenco; Y. S. Zubanova (Вавиловский журнал генетики и селекции, 2017)
Diploid wild relative of wheat – Aegilops speltoides – is a valuable source of genes for resistance to diseases. The synthetic form Avrodes (BBAASS) was used as a bridge to transfer leaf rust resistance genes from Ae. speltoides to common wheat. Introgression lines obtained from crosses of Avrodes and susceptible common wheat cultivars were evaluated in a field leaf rust nursery. Resistance levels varied from high to moderate. Testing of lines with the use of molecular markers has shown that some lines have the Lr28 and Lr35 genes inherited from synthetic form Avrodes. The majority of resistance lines have not been found to carry these genes. The Lr47 and Lr51 genes were not identified in the Avrodes and introgression lines. The analysis of chromosome pairing in F1 hybrids showed that the transfer of a genetic material from Avrodes to common wheat basically occurs through translocations. Lines with translocations on chromosomes 2D and 5D were identified by C-banding and FISH. The translocations differed in chromosomal location from known leaf resistance genes transferred to common wheat from Ae. speltoides. Hence it was assumed that new genes were introduced into the common wheat genome from Ae. speltoides. Introgression lines have been studied for productivity and technological qualities of grain. Lines AA60n9 and D37n10 combine high resistance to leaf rust with good characteristics of productivity and technological qualities of grain. The received results demonstrate a genetic diversity and a value of the investigated introgression lines for breeding of common wheat.